Murine Typhus: Clinical and epidemiological aspects (Colombia Medica, 2012)
Rickettsia typhi is an intracellular bacteria who causes murine typhus. His importance is reflected in the high frequency founding specific antibodies against R. typhi in several worldwide seroepidemiological studies, the seroprevalence ranging between 3-36%. Natural reservoirs of Rickettsia typhi are rats (some species belonging the Rattus Genus) and fleas (Xenopsylla cheopis) are his vector. This infection is associated with overcrowding, pollution and poor hygiene. Typically presents fever, headache, rash on trunk and extremities, in some cases may occur organ-specific complications, affecting liver, kidney, lung or brain. Initially the disease is very similar to other diseases, is very common to confuse the murine typhus with Dengue fever, therefore, ignorance of the disease is a factor related to complications or non-specific treatments for the resolution of this infection. This paper presents the most relevant information to consider about the rickettsiosis caused by Rickettsia typhi.